Global perspective of familial hypercholesterolaemia: a cross-sectional study from the EAS Familial Hypercholesterolaemia Studies Collaboration (FHSC) - Vallejo-Vaz, Antonio J.; Stevens, Christophe A.T.; Lyons, Alexander R.M.; Dharmayat, Kanika I.; Freiberger, Tomas; Hovingh, G. Kees; Le, Hong An (Elsevier B.V., 2021)
Background: The European Atherosclerosis Society Familial Hypercholesterolaemia Studies Collaboration (FHSC) global registry provides a platform for the global surveillance of familial hypercholesterolaemia through harmonisation and pooling of multinational data. In this study, we aimed to characterise the adult population with heterozygous familial hypercholesterolaemia and described how it is detected and managed globally. Methods: Using FHSC global registry data, we did a cross-sectional assessment of adults (aged 18 years or older) with a clinical or genetic diagnosis of probable or definite heterozygous familial hypercholesterolaemia at the time they were entered into the registries. Data were assessed overall and by WHO regions, sex, and index versus non-index cases. Findings: Of the 61 612 individuals in the registry, 42 167 adults (21 999 [53·6%] women) from 56 countries were included in the study. Of these, 31 798 (75·4%) were diagnosed with the Dutch Lipid Clinic Network criteria, and 35 490 (84·2%) were from the WHO region of Europe. Median age of participants at entry in the registry was 46·2 years (IQR 34·3-58·0); median age at diagnosis of familial hypercholesterolaemia was 44·4 years (32·5-56·5), with 40·2% of participants younger than 40 years when diagnosed. Prevalence of cardiovascular risk factors increased progressively with age and varied by WHO region. Prevalence of coronary disease was 17·4% (2·1% for stroke and 5·2% for peripheral artery disease), increasing with concentrations of untreated LDL cholesterol, and was about two times lower in women than in men. Among patients receiving lipid-lowering medications, 16 803 (81·1%) were receiving statins and 3691 (21·2%) were on combination therapy, with greater use of more potent lipid-lowering medication in men than in women. Median LDL cholesterol was 5·43 mmol/L (IQR 4·32-6·72) among patients not taking lipid-lowering medications and 4·23 mmol/L (3·20-5·66) among those taking them. Among patients taking lipid-lowering medications, 2·7% had LDL cholesterol lower than 1·8 mmol/L; the use of combination therapy, particularly with three drugs and with proprotein convertase subtilisin-kexin type 9 inhibitors, was associated with a higher proportion and greater odds of having LDL cholesterol lower than 1·8 mmol/L. Compared with index cases, patients who were non-index cases were younger, with lower LDL cholesterol and lower prevalence of cardiovascular risk factors and cardiovascular diseases (all p<0·001). Interpretation: Familial hypercholesterolaemia is diagnosed late. Guideline-recommended LDL cholesterol concentrations are infrequently achieved with single-drug therapy. Cardiovascular risk factors and presence of coronary disease were lower among non-index cases, who were diagnosed earlier. Earlier detection and greater use of combination therapies are required to reduce the global burden of familial hypercholesterolaemia. Funding: Pfizer, Amgen, Merck Sharp & Dohme, Sanofi-Aventis, Daiichi Sankyo, and Regeneron. © 2021 Elsevier Ltd
Keywords: Adult; Antibodies, Monoclonal, Humanized; Anticholesteremic Agents; Cholesterol, LDL; Coronary Disease; Cross-Sectional Studies; Europe; Female; Global Health; Heart Disease Risk Factors; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Hyperlipoproteinemia Type II; Male; Middle Aged; Proprotein Convertase 9; Registries; Treatment Outcome; atorvastatin; atorvastatin plus ezetimibe; ezetimibe; ezetimibe plus rosuvastatin; low density lipoprotein cholesterol; proprotein convertase subtilisin kexin type 9 inhibitor; rosuvastatin; serine proteinase inhibitor; unclassified drug; hydroxymethylglutaryl coenzyme A reductase inhibitor; hypocholesterolemic agent; low density lipoprotein cholesterol; monoclonal antibody; proprotein convertase 9; adult; age; Article; body mass; cardiovascular risk factor; cerebrovascular accident; child; cholesterol blood level; cohort analysis; controlled study; coronary artery disease; cross-sectional study; diabetes mellitus; familial hypercholesterolemia; female; heterozygosity; human; hypertension; major clinical study; male; middle aged; peripheral occlusive artery disease; prevalence; register; coronary artery disease; Europe; familial hypercholesterolemia; genetics; global health; register; treatment outcome